Lithium-ion conducting haloborooxysulfides

A haloboro-oxysulfide material with specific compositional formula addresses the challenge of achieving high lithium ion conductivity and stability in lithium batteries, enhancing battery performance by combining oxide and sulfide properties.

JP7605440B2Active Publication Date: 2024-12-24BASF SE +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021575340
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-17
Filing Date
2020-06-16
Publication Date
2024-12-24
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

Existing solid electrolytes for lithium batteries face challenges in achieving high lithium ion conductivity while maintaining chemical and electrochemical stability, particularly due to moisture sensitivity and decomposition issues in sulfide-based materials, and the need for a combination of oxide and sulfide properties.

Method used

Development of a haloboro-oxysulfide material with a general formula Li2x+zB2yM a O b*a S x+3y X z, where M is P, Si, Ge, or Sb, and X is a halide or pseudohalide, which exhibits favorable lithium ion conductivity and stability in direct contact with lithium metal and air.

Benefits of technology

The haloboro-oxysulfide material demonstrates high lithium ion conductivity, electrochemical stability, and resistance to moisture, offering improved performance in lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605440000004
    Figure 0007605440000004
  • Figure 0007605440000005
    Figure 0007605440000005
  • Figure 0007605440000006
    Figure 0007605440000006
Patent Text Reader

Abstract

Described are solid-state materials having ionic conductivity for lithium ions, methods for making said solid-state materials, methods for using said solid-state materials as solid electrolytes for electrochemical cells, solid-state structures selected from the group consisting of cathodes, anodes and separators for electrochemical cells, and electrochemical cells including such solid-state structures.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Described are solid-state materials having ionic conductivity for lithium ions, methods for making said solid-state materials, methods for using said solid-state materials as solid electrolytes for electrochemical cells, solid-state structures selected from the group consisting of cathodes, anodes and separators for electrochemical cells, and electrochemical cells including such solid-state structures. [Background technology]

[0002] The widespread use of all-solid-state lithium batteries has led to an increased demand for solid-state electrolytes with high conductivity for lithium ions. Important classes of such solid electrolytes are sulfide- and oxide-based glassy materials. In glassy solid electrolyte materials, the absence of crystalline pathways results in isotropic conduction with virtually no grain boundary resistance. The absence of grain boundaries in glassy electrolyte materials also prevents the formation of dendrites, since the amorphous electrolyte materials are obtained as dense, defect-free films by the melt-quenching technique. Typically, these materials contain Li2S in addition to glass formers such as B2S3. To increase the lithium ion concentration and ionic conductivity of the glass, lithium halide salts (e.g., LiX (where X=Cl, Br, I)) or lithium ortho-oxo salts (e.g., Li4SiO4, Li3PO4) are added.

[0003] Oxides and sulfides each exhibit certain desirable properties for a solid electrolyte, but also certain drawbacks. Oxides usually form a more stable structural framework resulting in better chemical and electrochemical stability, while sulfides usually have higher ionic conductivity and are easier to process. However, sulfide-based solid electrolytes usually suffer from poor air stability and are prone to decomposition due to their moisture sensitivity. Many sulfides react rapidly with moisture from the air and decompose, releasing H2S gas. Thus, there is a need for an electrolyte that combines the advantages of oxides and sulfides but eliminates their drawbacks. Summary of the Invention [Problem to be solved by the invention]

[0004] It is an object of the present disclosure to provide a solid-state material that can be used as a solid electrolyte for an electrochemical cell. Additionally provided are a method for producing said solid-state material, a method for using said solid-state material as a solid-state electrolyte for an electrochemical cell, a solid-state structure selected from the group consisting of a cathode, an anode and a separator for an electrochemical cell, and an electrochemical cell comprising such a solid-state structure, wherein said solid-state structure comprises said solid-state material. [Means for solving the problem]

[0005] According to a first aspect, the compound of general formula (I) Li 2x+z B 2y M a O b*a S x+3y X z (I) (In the formula, M is one or more selected from the group consisting of P, Si, Ge, As and Sb; X is one or more selected from the group consisting of halides and pseudohalides; x is in the range of 0.1 to 0.7, y is in the range of 0.05 to 0.5, z is in the range of 0.01 to 0.5, a is in the range of 0.01 to 0.5, preferably in the range of 0.05 to 0.48; b is in the range of 1.9 to 2.6, preferably in the range of 2 to 2.5; In one embodiment, a solid material is provided having a composition according to the invention, where 0.995≦x+y+z+a≦1.005, preferably where x+y+z+a=1.

[0006] Surprisingly, it has been found that the solid-state materials defined above exhibit favourable lithium ion conductivity as well as electrochemical stability in direct contact with lithium metal, and chemical stability to air and moisture.

[0007] Compositions according to general formula (I) can be considered to be oxysulfides, and more specifically, haloboro-oxysulfides.

[0008] The solid material as defined above, i.e. having a composition according to general formula (I), may be glassy.

[0009] Without being bound to any particular theory, Li2S-B2S3-MO b It is hypothesized that the phase diagram of the -LiX system, where M, b and X are as defined above, exhibits at least one glass-forming region, and that compositions according to general formula (I) are clearly within such region.

[0010] As used herein, the term "pseudohalide" refers to a monovalent anion that resembles a halide anion with respect to its chemical properties and therefore can be substituted for a halide anion in a compound without substantially changing the properties of such compound. The term "pseudohalide ion" is known in the art. See the IUPAC Goldbook. An example of a pseudohalide anion is N3 - , SCN - , C.N. - , OCN - , BF4 - and BH4 - In the case where the pseudohalide contains elements from the group consisting of B, S and O, the contents of B, S and O are not taken into account in the parameters x, y, a and b of general formula (I) defined above. In contrast, the total amount of halide and pseudohalide is indicated by the parameter "z" of general formula (I). In the pseudohalide-containing composition of general formula (I), the pseudohalide is preferably SCN - , BF4 - and BH4 - is selected from the group consisting of:

[0011] A solid material having a composition according to general formula (I) can be considered as a combination of (1) Li2S, (2) B2S3, (3) one or more oxides of M, and (4) one or more compounds LiX. Without wishing to be bound by any particular theory, it is currently hypothesized that in a solid material having a composition according to general formula (I), the oxide (3), where M is as defined above, may function as a secondary glass network former next to the primary glass network former B2S3 (2), while Li2S (1) functions as a glass network modifier, and LiX (4) provides additional lithium ions. Furthermore, the incorporation of the secondary glass network former reconstructs the thioborate network (the network formed by the primary glass network former B2S3) allowing the dissolution of a larger amount of LiX within the glass matrix, thereby increasing both the concentration and mobility of Li ions.

[0012] The solid material according to the first aspect defined above, i.e. having a composition according to general formula (I), may be amorphous. A material is called amorphous if it lacks the long-range order characteristic of a crystal, as indicated by the absence of well-defined reflections in its X-ray diffraction pattern. In this context, a reflection is considered well-defined if its intensity is 10% higher than the background.

[0013] The solid material according to the first aspect as defined above may also be accompanied by secondary and / or impurity phases having a composition not according to general formula (I) as defined above. In such cases, the volume fraction having a composition according to general formula (I) may be 50% or more, sometimes 80% or more, preferably 90% or more, most preferably 95% or more, based on the total volume of the solid material according to the first aspect as defined above and all secondary and impurity phases.

[0014] The second phase and the impurity phase may each be crystalline or amorphous. Typically, when the solid material having a composition according to the general formula (I) defined above is accompanied by a second phase and an impurity phase, respectively, at least one of the second phase and the impurity phase, respectively, is a crystalline phase. When a crystalline second phase and an impurity phase, respectively, are present, the volume fraction of the crystalline phase may be 20% or less, sometimes 10% or less, or 5% or less, or 1% or less, based on the total volume of the solid material having a composition according to the general formula (I) and all the second phases and the impurity phases. Typically, the solid material having a composition according to the general formula (I) is the only amorphous phase. When a crystalline second phase and an impurity phase, respectively, are present (e.g., LiI), the volume fraction of the solid material having a composition according to the general formula (I) can be determined by standard addition of a known crystalline material.

[0015] If present, the second and impurity phases are mainly composed of the precursors used to produce the solid material ((1) Li2S, (2) B2S3, or both B and S, (3) one or more oxides of M, where M is as defined above, (4) one or more compounds LiX, where X is as defined above, and intermediates formed from said precursors (e.g. B2S3, when B and S are provided in elemental form as precursor (2)), respectively, and possibly impurity phases that may originate from impurities of the precursors. For details of the production of the solid material of the first embodiment defined above, please refer to the information provided below in the context of the second embodiment of the present disclosure.

[0016] In certain solid state materials according to the first aspect defined above, M is selected from the group consisting of Si, P and Sb.

[0017] In certain solid state materials according to the first aspect defined above, X is selected from the group consisting of Cl, Br and I.

[0018] In the particular solid material according to the first aspect defined above, M is selected from the group consisting of Si, P and Sb, and X is selected from the group consisting of Cl, Br and I. Said particular solid material is composed of Li, B, M (wherein M is selected from the group consisting of Si, P and Sb), O, S and X (wherein X is selected from the group consisting of Cl, Br and I) in a molar ratio according to general formula (I):

[0019] In a particularly specific solid material according to the first aspect defined above, M is Si and X is selected from the group consisting of Cl, Br and I. Said specific solid material is composed of Li, B, Si, O, S and X (X is selected from the group consisting of Cl, Br and I) in molar ratios according to general formula (I):

[0020] The solid state material according to the first aspect defined above may have an ionic conductivity of at least 0.1 mS / cm, preferably at least 1 mS / cm at 25° C. The ionic conductivity is determined by conventional methods known in the art of battery materials development using electrochemical impedance spectroscopy (see the Examples section below for details).

[0021] At the same time, the solid-state material according to the first aspect defined above exhibits almost negligible electrical conductivity. More specifically, the electrical conductivity may be at least three orders of magnitude lower than the ionic conductivity, preferably at least five orders of magnitude lower than the ionic conductivity. In certain cases, the solid-state material according to the first aspect defined above exhibits a ionic conductivity of at least 10 -9 The electrical conductivity is determined by conventional methods known in the art of battery material development using direct current (DC) polarization measurements at different voltages (see the Examples section below for details).

[0022] With regard to lithium ion conductivity, it has been observed that the parameter "a" of general formula (I), which defines the content of the oxide of metal M (M is as defined above), is preferably in the range of 0.1 to 0.45, preferably 0.2 to 0.3.

[0023] With regard to the lithium ion conductivity, it has been observed that the parameter "z" of general formula (I), which defines the content of LiX (wherein X is as defined above), is preferably in the range of 0.26 to 0.41, preferably 0.33 to 0.4.

[0024] Preferably, the parameter "a" of general formula (I) defining the content of the oxide of metal M is in the range of 0.1 to 0.45, preferably 0.2 to 0.3, and the parameter "z" of general formula (I) defining the content of LiX is in the range of 0.26 to 0.41, preferably 0.33 to 0.4.

[0025] The solid material according to the first aspect defined above may be in the form of a monolithic glass, for example a fused cast monolithic glass.

[0026] The solid material according to the first aspect defined above may be in the form of a sheet. Preferably, said sheet is a thin sheet, for example with a thickness in the range 0.1 μm to 10 mm, for example 10 μm to 10 mm. Preferably, said sheet is free-standing.

[0027] In a particular group of solid-state materials according to the first aspect defined above, M is Si and X is I. Thus, the particular group of solid-state materials defined above has the general formula (Ia) Li 2x+z B 2y S a O b*a S x+3y I z (Ia) (In the formula, x is in the range of 0.1 to 0.3, y is in the range of 0.1 to 0.25, z is in the range of 0.2 to 0.48, preferably, z is in the range of 0.26 to 0.41; a is in the range of 0.08 to 0.5, preferably, a is in the range of 0.1 to 0.45; b is in the range of 1.95 to 2.05, preferably b is 2; 0.995≦x+y+z+a≦1.005, preferably x+y+z+a=1.

[0028] Surprisingly, it has been found that a particular group of solid-state materials as defined above exhibits favorable lithium ion conductivity as well as electrochemical stability in direct contact with lithium metal, and chemical stability to air and moisture.

[0029] The composition according to general formula (Ia) can be considered to be a lithium iodothioborosilicate.

[0030] The particular group of solid materials defined above, namely those having a composition according to general formula (Ia), may be glassy.

[0031] Without wishing to be bound by any particular theory, it is hypothesized that the phase diagram of the Li2S-B2S3-SiO2-LiI quaternary system exhibits at least one glass-forming region, and that compositions according to general formula (Ia) are clearly within such region.

[0032] A solid material having a composition according to general formula (Ia) can be considered as a combination of (1) Li2S, (2) B2S3, (3) an oxide of Si, and (4) LiI. Without wishing to be bound by any particular theory, it is currently hypothesized that in a solid material having a composition according to general formula (Ia), the oxide of Si (3) (typically SiO2) can function as a secondary glass network former next to the primary glass network former B2S3 (2), while Li2S (1) functions as a glass network modifier and LiI (4) provides additional lithium ions. Furthermore, the incorporation of the secondary glass network former SiO2 reconstructs the thioborate network (the network formed by the primary glass network former B2S3) to allow dissolution of a larger amount of LiI within the glass matrix, thereby increasing both the concentration and mobility of Li ions. Surprisingly, even the addition of a small amount of SiO2 can dissolve a significant amount of LiI within the glass matrix. Thus, SiO2 has strong glass-forming ability and is therefore a favorable secondary glass network former.

[0033] The particular group of solid materials defined above, i.e. solid materials having a composition according to general formula (Ia), may be amorphous. A material is called amorphous if it lacks the long-range order characteristic of a crystal, as indicated by the absence of well-defined reflections in its X-ray diffraction pattern. In this context, a reflection is considered well-defined if its intensity is 10% higher than the background.

[0034] The solid materials of the particular group defined above may also be accompanied by secondary and / or impurity phases having a composition not according to the general formula (Ia) defined above. In such cases, the volume fraction having a composition according to general formula (Ia) may be 50% or more, sometimes 80% or more, preferably 90% or more, most preferably 95% or more, based on the total volume of the solid materials of the particular group defined above and all secondary and impurity phases.

[0035] The second phase may be crystalline or amorphous. Typically, when the solid material having a composition according to the general formula (Ia) defined above is accompanied by a second phase and an impurity phase, respectively, at least one of the second phase and the impurity phase, respectively, is a crystalline phase. When a crystalline second phase and an impurity phase, respectively, are present, the volume fraction of the crystalline phase may be 20% or less, sometimes 10% or less, preferably 5% or less, most preferably 1% or less, based on the total volume of the solid material having a composition according to the general formula (Ia) and all the second phases and the impurity phases. Typically, the solid material having a composition according to the general formula (I) is the only amorphous phase. When a crystalline second phase and an impurity phase, respectively, are present (e.g., LiI), the volume fraction of the solid material having a composition according to the general formula (Ia) may be determined by standard addition of a known crystalline material.

[0036] When present, the second and impurity phases are mainly composed of the precursors (Li2S, S, B, SiO2, LiI) used to produce the solid material and of the intermediates formed from said precursors (e.g. B2S3), respectively, and possibly impurity phases that may originate from impurities of the precursors. For details of the production of the particular family of solid materials defined above, please refer to the information provided below in the context of the second aspect of the present disclosure.

[0037] The particular group of solid-state materials defined above may have an ionic conductivity of 0.1 mS / cm or more, preferably 1 mS / cm or more at 25° C. The ionic conductivity is determined by conventional methods known in the art of battery materials development using electrochemical impedance spectroscopy (see the Examples section below for details).

[0038] At the same time, the solid-state materials of the particular group defined above exhibit almost negligible electrical conductivity. More specifically, the electrical conductivity may be at least three orders of magnitude lower than the ionic conductivity, preferably at least five orders of magnitude lower than the ionic conductivity. In certain cases, the solid-state materials of the particular group defined above exhibit a conductivity of at least 10 -9The electrical conductivity is determined by conventional methods known in the art of battery material development using direct current (DC) polarization measurements at different voltages (see the Examples section below for details).

[0039] With regard to lithium ion conductivity, it has been observed that the parameter "a" of general formula (Ia), which defines the content of silicon oxide (typically SiO2), is preferably in the range of 0.1 to 0.45, preferably 0.2 to 0.3.

[0040] With regard to lithium ion conductivity, it has been observed that the parameter "z" of general formula (Ia), which defines the LiI content, is preferably in the range of 0.26 to 0.41, preferably 0.33 to 0.4.

[0041] Preferably, the parameter "a" of general formula (Ia), which defines the content of silicon oxide (typically SiO2), is in the range of 0.1 to 0.45, preferably 0.2 to 0.3, and the parameter "z" of general formula (Ia), which defines the content of LiI, is in the range of 0.26 to 0.41, preferably 0.33 to 0.4.

[0042] The particular group of solid materials defined above may be in the form of monolithic glass, for example fusion cast monolithic glass.

[0043] The particular group of solid materials defined above may be in the form of a sheet. Preferably, said sheet is a thin sheet, for example with a thickness in the range 0.1 μm to 10 mm, for example 10 μm to 10 mm. Preferably, said sheet is free-standing.

[0044] Preferred solid materials according to the first aspect defined above are those which have one or more of the particular characteristics disclosed above.

[0045] According to a second aspect, there is provided a method for obtaining a solid material according to the first aspect defined above, said method comprising the steps of: a) Precursor (1) Li2S (2) B2S3, or both boron and sulfur (3) One or more oxides of an element M selected from the group consisting of P, Si, Ge, As, and Sb. (4) one or more compounds LiX, where X is selected from the group consisting of halides and pseudohalides; A method of preparing b) a method step of producing a mixture comprising the precursor provided in step a), the molar ratios of the elements Li, S, B, M, O and X in said mixture conforming to general formula (I), c) a process step of heat treating the mixture produced in process step b) to obtain a melt, d) a method step of quenching the melt obtained in step c) so as to obtain a solid material having a composition according to general formula (I). Includes.

[0046] The process according to the second aspect defined above is called "melt-quench". Such a process is cost-effective and easily scalable. It makes it possible to obtain solid materials in the form of particularly thin sheets, for example vitreous sheets, with a thickness in the range of 0.1 μm to 10 mm, for example 10 μm to 10 mm. Preferably, said sheets are free-standing.

[0047] In step a) of the method according to the second aspect defined above, a precursor for the mixture to be produced in step b) is provided, said precursor comprising: (1) Li2S (2) B2S3, or both B and S, i.e., either the compound B2S3, or the elemental forms of B and S, respectively. (3) One or more oxides of an element M selected from the group consisting of P, Si, Ge, As, and Sb. (4) one or more compounds LiX, where X is selected from the group consisting of halides and pseudohalides; It is.

[0048] In a particular method according to the second aspect defined above, the one or more oxides (3) are selected from the group consisting of oxides of Si, P and Sb.

[0049] In certain methods according to the second aspect defined above, the one or more compounds LiX(4) are selected from LiCl, LiBr and LiI.

[0050] In a particular method according to the second aspect defined above, the one or more oxides (3) are selected from the group consisting of oxides of Si, P and Sb; the one or more compounds LiX are selected from LiCl, LiBr and LiI.

[0051] In a particularly particular method according to the second aspect defined above, the oxide is SiO2 and the one or more compounds LiX are selected from LiCl, LiBr and LiI. In said particularly particular method, the precursors provided in step a) may be (1) Li2S, (2) S and B, each in elemental form, (3) SiO2, and (4) one or more of LiCl, LiBr and LiI.

[0052] In step b) of the method according to the second aspect as defined above, a mixture is prepared comprising the precursors (1) to (4) provided in step a) as defined above, in which the molar ratios of the elements Li, S, B, M (M as defined above), O and X (X as defined above) comply with the general formula (I).

[0053] In a particular case, said mixture produced in step b) consists of the precursors (1) to (4) provided in step a).

[0054] In step b), the mixing can be carried out by means of mechanical comminution, for example by means of ball milling.

[0055] In step b), it is useful that any handling is carried out under a protective gas atmosphere.

[0056] In step b), the mixture containing the precursors can be formed into pellets, which are heat treated in step c).

[0057] In step c) of the process according to the second aspect defined above, the mixture produced in process step b) is heat treated to obtain a melt, typically a vitreous melt. Step c) therefore involves a heat treatment at a temperature higher than the melting temperature of the mixture produced in step b).

[0058] The heat treatment may be carried out in a closed vessel, which may be a sealed quartz tube or any other type of vessel that can withstand the temperatures of the heat treatment and is not prone to react with the components of the glass, such as a vitreous carbon crucible or a tantalum crucible.

[0059] Preferably, step c) comprises - a first step of heat treatment at a temperature in the range of 400°C to 650°C for a period of 1 to 13 hours, preferably 5 to 13 hours and - a second step of heat treatment at a temperature in the range of 700°C to 1000°C, preferably in the range of 700°C to 900°C, for a period of 1 to 40 hours, preferably 20 to 30 hours. Includes.

[0060] In step d) of the process according to the second embodiment defined above, the melt obtained in step c) is quenched so as to obtain a solid material having a composition according to general formula (I).

[0061] Quenching can be carried out by contacting the melt obtained in step c) with water, ice, a supercooled gas (e.g. liquid nitrogen or liquid argon), a metal plate or a chemically inert mould (e.g. a mould made of a corrosion-resistant material, preferably a mould made of metal) so as to achieve rapid cooling.

[0062] Upon quenching, the melt obtained in step c) can be formed into a monolithic glass, for example a melt cast monolithic glass.

[0063] Upon quenching, the melt obtained in step c) can be formed into a glass sheet, which can be obtained in the form of a continuous sheet, which is then cut to the desired size.

[0064] The particular method according to the second aspect as defined above is suitable for producing a solid material of the particular above defined group of solid materials according to the first aspect as defined above.

[0065] In step a) of said particular method according to the second aspect as defined above, suitable for producing a solid-state material of the particular group as defined above of solid-state materials according to the first aspect as defined above, the precursor provided in step a) is (1) Li2S (2) Boron and sulfur, both in elemental form, or B2S3 (3) SiO2 (4) LiI It is.

[0066] In step b) of said particular method according to the second aspect as defined above, suitable for producing a solid-state material of the particular group defined above of solid-state materials according to the first aspect as defined above, a mixture is produced comprising precursors (1) to (4) provided in step a) as defined above, wherein in said mixture produced in step b) the molar ratios of the elements Li, S, B, Si, O and I comply with the general formula (Ia):

[0067] In a particular case, said mixture produced in step b) consists of the precursors (1) to (4) provided in step a) as defined above.

[0068] In step b), the mixing can be carried out by means of mechanical comminution, for example by means of ball milling.

[0069] In step b), it is useful that any handling is carried out under a protective gas atmosphere.

[0070] In step b), the mixture containing the precursors may be formed into pellets, which are heat treated in step c).

[0071] In step c) of said particular process according to the second aspect defined above, the mixture produced in process step b) is heat treated to obtain a melt, typically a vitreous melt. For further details of step c), reference is made to the disclosure provided above.

[0072] In step d) of said particular method according to the second embodiment defined above, the melt obtained in step c) is quenched so as to obtain a solid material having a composition according to general formula (Ia). For further details of step d), reference is made to the disclosure provided above.

[0073] Preferred processes according to the second aspect defined above are those having one or more of the particular features disclosed above.

[0074] The solid-state material according to the first aspect defined above, respectively obtained by the method according to the second aspect defined above, can be used as a solid electrolyte for an electrochemical cell. In this specification, the solid-state electrolyte can form a component of a solid-state structure for an electrochemical cell, said solid-state structure being selected from the group consisting of a cathode, an anode and a separator. Thus, the solid-state material according to the first aspect defined above, respectively obtained by the method according to the second aspect defined above, can be used alone or in combination with additional components to produce a solid-state structure for an electrochemical cell, such as a cathode, an anode or a separator.

[0075] Thus, the present disclosure further provides a method of using a solid material according to the first aspect defined above, respectively obtained by a method according to the second aspect defined above, as a solid electrolyte for an electrochemical cell. More specifically, the present disclosure further provides a method of using a solid material according to the first aspect defined above, respectively obtained by a method according to the second aspect defined above, as a component of a solid structure for an electrochemical cell, said solid structure being selected from the group consisting of a cathode, an anode and a separator.

[0076] In the context of this disclosure, the electrode that develops a net negative charge during discharge is called the anode, and the electrode that develops a net positive charge during discharge is called the cathode. A separator electrically separates the cathode and anode from each other within the electrochemical cell.

[0077] The cathode of an all-solid-state electrochemical cell typically comprises a solid electrolyte as an additional component next to the active cathode material, and the anode of an all-solid-state electrochemical cell typically comprises a solid electrolyte as an additional component next to the active anode material.

[0078] The morphology of the solid-state structures for electrochemical cells, particularly for all-solid-state lithium batteries, is determined in particular by the morphology of the produced electrochemical cell itself.

[0079] The present disclosure further provides a solid-state structure for an electrochemical cell selected from the group consisting of a cathode, an anode and a separator, comprising a solid-state material according to the first aspect defined above, each obtained by a method according to the second aspect defined above.

[0080] The present disclosure further provides an electrochemical cell comprising a solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, in which the solid-state material according to the first aspect defined above, respectively obtainable by a method according to the second aspect defined above, may form one or more solid structural components selected from the group consisting of a cathode, an anode and a separator.

[0081] The electrochemical cell defined above comprises the following components: α) at ​​least one anode, β) at least one cathode; γ) at least one separator; wherein at least one of the three constituents is a solid structure comprising a solid material according to the first aspect as defined above, each obtained by a method according to the second aspect as defined above.

[0082] Suitable electrochemically active cathode materials and suitable electrochemically active anode materials are known in the art. In such electrochemical cells, the anode α) may comprise graphitic carbon, metallic lithium or a metal alloy containing lithium as the anode active material.

[0083] Such electrochemical cells may be alkali metal containing cells, in particular lithium ion containing cells. In lithium ion containing cells, charge transport is via Li + Affected by ions.

[0084] Due to its excellent electrochemical stability in direct contact with lithium metal, in certain preferred cases of the solid-state structures defined above, the solid-state material according to the first aspect defined above, respectively obtained by the method according to the second aspect defined above, may be in direct contact with an anode comprising lithium metal, thus eliminating the need for a protective layer between them. Thus, in an all-solid-state battery, the solid-state material according to the first aspect defined above, respectively obtained by the method according to the second aspect defined above, may be applied as a solid electrolyte or as a component of a solid electrolyte in direct contact with an anode comprising lithium metal or an alloy comprising lithium metal. Due to the excellent electrochemical stability of said solid electrolyte in direct contact with lithium metal, such all-solid-state batteries may exhibit favorable cycle stability, coulombic efficiency and capacity retention over a large number of cycles.

[0085] The electrochemical cell may have a disk-like or prismatic shape. The electrochemical cell may include a housing, which may be made of steel or aluminum.

[0086] A plurality of electrochemical cells as described above can be combined into an all-solid-state battery having both solid electrodes and solid electrolytes. A further aspect of the present disclosure refers to a battery, more specifically an alkali metal ion battery, in particular a lithium ion battery, comprising at least one electrochemical cell as described above, such as two or more electrochemical cells as described above. The electrochemical cells as described above can be combined with each other in an alkali metal ion battery, for example in series or parallel connection. A series connection is preferred.

[0087] The electrochemical cells, respectively the batteries described herein, can be used to make or operate automobiles, computers, personal digital assistants, cell phones, watches, video recorders, digital cameras, thermometers, calculators, laptop BIOS, communications devices, or remote car locks, and for stationary applications such as energy storage devices in power plants. Another aspect of the invention is a method of making or operating automobiles, computers, personal digital assistants, cell phones, watches, video recorders, digital cameras, thermometers, calculators, laptop BIOS, communications devices, remote car locks, and for stationary applications such as energy storage devices in power plants, using at least one battery of the invention or at least one electrochemical cell of the invention.

[0088] A further aspect of the present disclosure is a method of using an electrochemical cell as described above in an automotive vehicle, a bicycle powered by an electric motor, a robot, an aircraft (e.g., an unmanned aerial vehicle including a drone), a watercraft, or a stationary energy storage.

[0089] The present disclosure further provides a device that comprises at least one electrochemical cell of the present invention as described above.Preferably, the mobile device is a vehicle, such as a car, a bicycle, an airplane, or a water vehicle, such as a ship or a boat.Other examples of mobile devices are portable, such as a computer, especially a laptop, a phone, or a power tool, such as in the construction sector, especially a drill, a battery-powered screwdriver, or a battery-powered tacker.

[0090] The present invention is further illustrated by the following non-limiting examples. EXAMPLES

[0091] 1.Material Production Process a) Precursor of (1)Li2S (Sigma Aldrich, 99.98%) (2) Boron (Sigma Aldrich 99%) and Sulfur, both in elemental form (3) SiO2 (4) LiI We have prepared the following.

[0092] Step b) The mixture of precursors provided in step a) was prepared by grinding the precursors together in amounts such that the molar ratio of the elements Li, S, B, M, O and X in the resulting mixture complies with general formula (I).

[0093] For comparison, mixtures were prepared without adding SiO2.

[0094] Each mixture was pelletized.

[0095] All handling of powders was carried out inside an argon-filled glove box.

[0096] Process c) For heat treatment, the pelletized mixtures obtained in step b) were placed in glassy carbon crucibles, which were then placed in quartz tubes. Each quartz tube was sealed under vacuum and placed vertically in a furnace. The quartz tubes were heated to 500°C and held for 12 hours, then at 800°C for 20 hours.

[0097] Step d) After the heat treatment was completed, the resulting melt was quenched in ice water.

[0098] The resulting material was in powder form. For details of the composition of the resulting material, see the table below.

[0099] 2. Ionic and electrical conductivity The bulk resistance of the obtained samples of solid material was determined by electrochemical impedance spectroscopy using a Bio-logic MTZ-35 impedance analyzer at a frequency range of 10 MHz to 100 mHz with an amplitude of 100 mV. Measurements were carried out in the temperature range of 25 °C to 80 °C. The samples were obtained by pelletizing the powdered material in a custom-made Swagelok cell of 10 mm diameter. To record the impedance spectra, the samples were sandwiched between two pieces of indium foil to obtain good contact at variable temperatures. The lithium ion conductivity was calculated from the bulk resistance of the samples.

[0100] The lithium ion conductivity of all samples measured at 25° C. is shown in Tables 1 and 2 below:

[0101] [Table 1]

[0102] [Table 2]

[0103] In Tables 1 and 2, "I content" represents the content of iodine (I).

[0104] The data in the table and Figure 1 (a plot of ionic conductivity versus SiO2 content for the materials in Table 2) show that ionic conductivity is significantly affected by SiO2 content (parameter "a" in formula (Ia)). Adding small amounts of SiO2 increases ionic conductivity significantly. Without wishing to be bound by theory, this effect is seen to be greater than that of the comparative material Li without SiO2. 1.06 B 0.48 S 1.02 I 0.46 This is attributed to improved glass formation due to the presence of the secondary glass network former SiO2, as compared to SiO2. The ionic conductivity decreases slightly after passing the maximum and then remains at a fairly high level, but eventually decreases significantly as the SiO2 content is increased further.

[0105] In addition, as can be seen from the table, increasing LiX content increases the ionic conductivity.

[0106] The electrical conductivity was determined by DC polarization using a custom-made cell with a diameter of 10 mm, in which the powder was compressed between two stainless steel pistons. For each measurement, voltages of 0.125, 0.25, 0.5, and 0.75 V were applied for 1 h each. 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37 (the material with the highest ionic conductivity) has an electrical conductivity of 5.93 * 10 -9 S / cm was measured, which is more than five orders of magnitude lower than the ionic conductivity (2.05 mS / cm, see Table 2).

[0107] 3. X-ray Diffraction To record the XRD patterns, the powder samples were placed in a zero background holder and sealed with Kapton film. Diffraction patterns were measured on a Pan Analytical Empryean X-ray diffractometer of the Bragg-Brentano type using CuK alpha radiation in the range 5°2-theta to 90°2-theta.

[0108] FIG. 2 shows the XRD patterns of a set of samples with different SiO2 contents a (for composition details, see Table 2 above).

[0109] In this set of samples, the glass-forming region extends from a = 0.2 to a = 0.43, as evidenced by the lack of sharp reflections in the XRD patterns. For SiO2 contents a outside this range, the material can be considered as composite due to the appearance of reflections from each of the second and impurity phases observed in the XRD patterns.

[0110] The decrease in the sharp reflection of the LiI second phase when the SiO2 content a increases from 0 to 0.2 clearly indicates that the poor glass network formation of the comparative material without SiO2 is already significantly improved by a small amount of SiO2. The better the glass network formation, the more LiI is incorporated into the glass network, which results in the disappearance of the reflection of the LiI second phase (see Fig. 2) and the increase in ionic conductivity (see Fig. 1).

[0111] Since the XRD patterns of materials with a in the range of 0.2 to 0.43 (glass-forming region) show no or only very weak reflections, LiI is presumed to be almost completely dissolved in the glass matrix.

[0112] At a SiO2 content of 0.43, the reflections of LiI and SiO2 appear in the XRD patterns and become more prominent with increasing SiO2 content (see Figure 2). Clearly, LiI and SiO2 start to crystallize from the glass network. Above a = 0.43, the samples behave like nanocomposites and likely contain crystalline SiO2 and LiI nanodomains that disrupt the lithium ion conduction pathways and significantly reduce the conductivity (see Figure 1).

[0113] As is evident from Fig. 1, samples with compositions falling within the glass-forming region exhibit favorable ionic conductivity, with a maximum at a SiO2 content of a = 0.23, which corresponds to the lower limit of the glass-forming region. The decrease in lithium ion conductivity with further increase in SiO2 content within the glass-forming region is probably due to a correlated decrease in the proportion of LiI in the total composition.

[0114] Adding more SiO2 within the glass-forming region is not advantageous from the standpoint of ionic conductivity, but may be advantageous from the standpoint of chemical stability (see below).

[0115] 4. Air stability The samples were obtained by compressing 100 mg of powdered material into a 10 mm diameter pellet. To test the stability to air, the samples were placed in a three-necked round-bottom flask. The air pump was run in reverse, allowing ambient air to flow into the three-necked round-bottom flask. The second neck of the flask contained a probe that was directly connected to a H2S sensor (BW GasAlertMicro 5 Multi-Gas Detector). To ensure accurate H2S monitoring, the probe was placed directly above the sample. The third neck was used as an exhaust / blowout outlet. The air temperature was approximately 23-25 ​​°C and the relative humidity was 40-50%. H2S evolution from the samples upon air exposure was monitored for approximately 3 h.

[0116] For comparison, β-Li3PS4 (prepared by solution processing, see WO2018 / 054709A1) and Li7P3S 11 Samples of were also tested.

[0117] The test results are shown in Figure 3.

[0118] As expected, Li7P3S 11 demonstrated poor stability, exhibiting rapid H2S evolution at levels above 10 ppm in the first 5 minutes. The experiment was shortened after 100 minutes as H2S levels reached over 200 ppm, exceeding the detector limits. In contrast, β-Li3PS4 showed no observable H2S evolution. This may be due to residual solvent in the material due to the low processing temperature, which helps to stabilize the material in the presence of atmospheric moisture.

[0119] In contrast, composition Li 0.77 B 0.39 S 0.23 O 0.46 S 0.77 I 0.5 The sample showed 5 ppm H2S generation for 3 hours and had a composition of Li 0.5 B 0.25 S 0.5 OSI 0.25The sample of Li3PS4 showed almost the same low H2S evolution as β-Li3PS4, except for a temporary increase to 2 ppm H2S after 1 hour of air exposure. However, the composition Li 0.5 B 0.25 S 0.5 OSI 0.25 exhibited low lithium ion conductivity.

[0120] Apparently, increasing the number of silicate groups increases the chemical stability at the trade-off with ionic conductivity.

[0121] It should be noted that Li-ion batteries are typically processed under dry room conditions with significantly less moisture (<1% relative humidity), but the experiments performed here represent somewhat extreme conditions. Therefore, the thioiodoborosilicates studied here appear promising, as they can be reasonably expected to produce little or no H2S within the time limits required for battery assembly.

[0122] 5. Microscopy Li 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37 Scanning electron microscope images of particles of (the material exhibiting the highest ionic conductivity) and accompanying energy dispersive X-ray analysis (EDX) (not shown) and scanning transmission electron microscopy (STEM) analysis with electron energy loss spectroscopy (EELS) (not shown) showed that the studied materials exhibit a high degree of uniformity of elemental distribution at the submicron scale.

[0123] 6.Thermal stability Quantities of 5-10 mg of solid material were placed in aluminum pans and hermetically sealed in an argon-filled glove box using a Tzero sample press. Differential scanning calorimetry (DSC) was performed under nitrogen flow using a TA Instruments Q2000 DSC. Samples were heated from 25 °C to 500 °C at a rate of 5 °C / min.

[0124] The thermal stability of glass is determined by the softening (glass transition) temperature (T g ) and stability to crystallization, which is determined by the onset temperature of crystallization (T x ) and glass transition temperature (T g ) is determined by the temperature difference between

[0125] The glass transition temperature (T g ), crystallization initiation temperature (T x ) and melting temperature T l are summarized in Table 3. g T corresponds to the temperature at which the maximum slope of the decline in the DSC baseline occurs before the exothermic crystallization peak. x corresponds to the onset of crystallization from LiI recrystallizing from the glass network. The recrystallization of LiI was confirmed by XRD (not shown). l does not correspond to the melting of the glass itself, but to the melting of LiI that was previously recrystallized from the glass.

[0126] As the SiO2 content increases from a = 0 to a = 0.2, T g increases, T x and T l It can be seen from Table 3 that when the SiO2 content is further increased to a = 0.27, T x increases further, but T g and T l changes only slightly. T g In contrast to T x The increase in the thermal stability parameter, ΔT x (T x -T g ) increases, implying that increasing the SiO2 content increases the stability of the glass network with respect to recrystallization. When the SiO2 content is further increased to a = 0.33, T g and T x decreases somewhat, but T l And the thermal stability parameters change only slightly.

[0127] [Table 3]

[0128] 7. Electrochemical Studies Li 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37 (the material with the highest ionic conductivity) was subjected to electrochemical studies.

[0129] The interfacial reactivity of a solid electrolyte in contact with lithium metal is described by a symmetric Li|solid electrolyte|Li cell (where the solid electrolyte is Li 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37 The solid electrolyte was evaluated using a combination of electrochemical impedance spectroscopy (EIS) in conjunction with galvanostatic cycling measurements of either β-Li3PS4 (according to the invention) or β-Li3PS4 (for comparison). Symmetric cells were assembled in a glove box filled with an argon atmosphere. The solid electrolyte was compressed under a 2 ton load in a 10 mm diameter PEEK cylinder for 1 min to form a pellet with a thickness of about 0.12 mm. Li metal foil (Sigma Aldrich) was pressed onto either side of the pellet in contact with the solid electrolyte. This assembly Li-foil|solid electrolyte|Li-foil was sandwiched between two stainless steel rods and held under pressure using a custom-made device. The cell was clamped with a torque wrench set to a torque of 4 N·m. Galvanostatic cycling of the cell was performed at room temperature using a Bio-Logic VMP-3. The cell according to the invention was subjected to a current density of 0.1 mA / cm. 2 at 0.1mAh / cm 2 The comparative cell was subjected to constant current cycling at a current density of 0.1 mA / cm 2 at 0.05mAh / cm 2The cells were galvanostatically cycled to an areal capacity of 1000 . At the same time, the resistance of each cell was measured every 5 cycles using electrochemical impedance spectroscopy at an applied voltage of 100 mV. Figure 4 shows the evolution of cell resistance with increasing cycle time (measured every 5 cycles). The top graph is for a comparative cell and the bottom graph is for a cell according to the invention.

[0130] The cell according to the invention exhibits stable cycling (lithium stripping / plating) for 110 hours at a polarization voltage (10 mV) ten times lower than the control cell (100 mV). Most of this difference is due to the Li 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37The resistance of the comparative cell appears to fluctuate but increases during cycling. The increase in the resistance of the comparative cell may be due to the formation of a passivation interphase composed of Li2S and Li3P, which is known in the art for β-Li3PS4 (see, for example, Z. Liu, W. Fu, E. P. Payzant, X. Yu, Z. Wu, N. J. Dudney, J. Kiggans, K. Hong, A. J. Rondinone, C. Liang, J. Am. Chem. Soc. 2013, 135, 975) and is known in the art (see, for example, K. N. Wood, K. X. Steirer, S. E. Hafner, C. Ban, S. Santanagopalan, S. H. Lee, G. Teeter, Nat. Commun. 2018, 9, 2490). Due to its formation of a passivating interphase, β-Li3PS4 is widely regarded as one of the most stable solid electrolytes in contact with Li metal, compared to other state-of-the-art solid electrolytes (see, for example, S. Wenzel, DA Weber, T. Leichtweiss, MR Busche, J. Sann, J. Janek, Solid State Ionics 2016, 286, 24; S. Wenzel, S. Randau, T. Leichtweiss, DA Weber, J. Sann, WG Zeier, J. Janek, Chem. Mater. 2016, 28, 2400; and S. Wenzel, T. Leichtweiss, D. Krueger, J. Sann, J. Janek, Solid State Ionics 2015, 278, 98). In contrast, the cells according to the invention do not show a significant increase in resistance during cycling. This effect can be attributed to the incorporation of LiI into the solid electrolyte of the cell according to the invention.

[0131] The battery cycle test was performed on the anode made of Li-In alloy, Li 0.85 B 0.38 S 0.2 O 0.4 S 0.82 I 0.37 Solid electrolyte layer (separator) and solid electrolyte Li 0.85 B 0.38 S0.2 O 0.4 S 0.82 I 0.37 The experiment was carried out in an all-solid-state cell with a cathode made of a composite material fabricated by mixing TiS (Sigma Aldrich, 99.9%, particle size 75 μm) in a 1:1 mass ratio. The cathode composite (8 mg; 5.13 mg / cm) 2 The TiS2 content corresponding to 1000 mg / cm2 and the solid electrolyte (60 mg) were compressed in a 10 mm diameter PEEK cylinder to form a bilayer pellet. The anode Li-In alloy had the target composition Li 0.5 The cell was then sandwiched between two stainless steel rods and held under pressure using a custom-made device. The cell was allowed to rest for 8 hours before cycling to allow the cell to relax. The areal capacity of the cell was 1.2 mAh / cm. 2 Galvanostatic cycling (charge / discharge) of the cells was performed at room temperature using a Bio-Logic VMP-3. The cells were charged and discharged at C / 10 at room temperature (approximately 25°C) over the voltage range of 0.9-2.4 V vs. Li-In (1.5-3 V vs. Li).

[0132] Charge-discharge curves for cycles 1, 2, 5, 10, 20 and 50 are shown in Figure 5. After the first charge cycle at 2.7 V vs Li, a small irreversible capacity (6 mAh / g) is evident, which is due to the initial electrolyte oxidation at the cathode interface. The potential at which this irreversible capacity is observed is S 2-This is similar to what has been observed in thiophosphate-based electrolytes where Li-In undergoes oxidation (see, for example, W.D. Richards, L.J. Miara, Y.Wang, J.C. Kim, G.Ceder, Chem. Mater. 2015, 28, 266; and R.Koerver, F.Walther, I.Ayguen, J.Sann, C.Dietrich, W.G.Zeier, J.Janek, J.Mater.Chem.A 2017, 5, 22750). This irreversible process that occurs during the first charge cycle is more clearly seen in the corresponding dQ / dV plot shown in Figure 6. The peak at 2.15 V vs Li-In shows a rapid decrease in intensity after the first cycle and disappears completely by the 10th cycle, suggesting the formation of a stable cathode-electrolyte interface.

[0133] After the first cycle, the cell exhibits excellent cycling performance at C / 10 (top graph in Figure 7), with virtually no capacity loss over three months of cycling. The cell maintains a capacity of approximately 239 mAh / g (theoretical capacity of TiS2: 240 mAh / g) for over 130 cycles (bottom graph in Figure 7), with a high coulombic efficiency averaging 99.9%.

[0134] The rate performance of the same all-solid-state cell cycled within the same voltage range and at 25 °C is shown in Figure 8. The cell initially cycled at C / 5 achieved a capacity of 213 mAh / g, representing 90% capacity retention when the current density was doubled. Subsequent increases in current density to a 1C rate retained 75% of the capacity, and returning to the initial C / 5 rate fully restored the capacity. [Brief description of the drawings]

[0135] [Figure 1] FIG. 1, a plot of ionic conductivity versus SiO2 content for the materials in Table 2, shows that ionic conductivity is significantly affected by SiO2 content (parameter "a" in formula (Ia)). [Diagram 2] FIG. 2 shows the XRD patterns of a set of samples with different SiO2 contents a (for composition details, see Table 2 above). [Diagram 3] For comparison, samples of β-Li3PS4 (prepared by solution processing, see WO2018 / 054709A1) and Li7P3S11 were also tested, and the results are shown in Figure 3. [Figure 4] FIG. 4 shows the evolution of cell resistance with increasing cycle time (measured every 5 cycles). [Diagram 5] The charge-discharge curves for cycles 1, 2, 5, 10, 20 and 50 are shown in FIG.

Claims

1. General formula (I) Li 2x+z B 2y M a O b*a S x+3y X z (I) (In the formula, M is Si; X is one or more selected from the group consisting of Cl, Br and I; x is in the range of 0.1 to 0.7; y is in the range of 0.05 to 0.5; z is in the range of 0.01 to 0.5; a is in the range of 0.01 to 0.5; b is in the range of 1.9 to 2.6; 0.995≦x+y+z+a≦1.005) A solid material having a composition according to

2. 2. The solid material of claim 1, wherein the solid material having a composition according to general formula (I) is glassy.

3. General formula (Ia) Li 2x+z B 2y Si a O b*a S x+3y I z (Ia) (In the formula, x is in the range of 0.1 to 0.3; y is in the range of 0.1 to 0.25; z is in the range of 0.2 to 0.48; a is in the range of 0.08 to 0.5; b is in the range of 1.95 to 2.05; 0.995≦x+y+z+a≦1.005) 3. The solid material according to claim 1, having a composition according to

4. The solid material according to claim 1 , having an ionic conductivity of 0.1 mS / cm or more at 25° C.

5. 5. The solid material according to claim 1 in the form of a sheet.

6. A method for producing a solid material according to any one of claims 1 to 5, comprising the steps of: a) Precursor Li 2 S B 2 S 3 , or both boron and sulfur Oxide of Si as element M one or more compounds LiX, where X is selected from the group consisting of Cl, Br and I; preparing b) preparing a mixture comprising the precursors provided in step a), the molar ratios of the elements Li, S, B, M, O and X in said mixture conforming to general formula (I); c) heat treating the mixture produced in step b) to obtain a melt; d) quenching the melt obtained in step c) so as to obtain a solid material having a composition according to general formula (I). A method comprising:

7. The precursor provided in step a) is Li 2 S, S, B, and SiO 2 and one or more of LiCl, LiBr and LiI; and / or In step b), the mixing is carried out by means of mechanical grinding; and / or In step c), the heat treatment is carried out in a closed vessel; and / or In step d), quenching is carried out by contacting the melt obtained in step c) with water, ice, supercooled gas, a metal plate or a chemically inert mould; The method according to claim 6.

8. Step c) is a first step of heat treatment at a temperature ranging from 400°C to 650°C for a period of 1 to 13 hours; and A second step of heat treatment at a temperature ranging from 700°C to 1000°C for a period ranging from 1 to 40 hours. The method of claim 6 or 7, comprising:

9. said heat treatment of said first stage being carried out for a period of 5 to 13 hours; 9. The method of claim 8, wherein the heat treatment of the second stage is carried out for a period of 20 to 30 hours.

10. The method according to claim 8 or 9, wherein the heat treatment of the second stage is carried out in the range of 700°C to 900°C.

11. 11. The method according to any one of claims 7 to 10, wherein in step b) the mixture comprising the precursor is formed into pellets which are heat treated in step c).

12. 12. The method according to any one of claims 7 to 11, wherein in step b) any handling is carried out under a protective gas atmosphere.

13. 6. Use of the solid material according to any one of claims 1 to 5 as a solid electrolyte for an electrochemical cell, wherein the solid electrolyte is a component of a solid structure for the electrochemical cell selected from the group consisting of a cathode, an anode and a separator.

14. A solid-state structure for an electrochemical cell, selected from the group consisting of a cathode, an anode and a separator, comprising a solid-state material according to any one of claims 1 to 5.

15. 15. An electrochemical cell comprising a solid-state material according to any one of claims 1 to 5, wherein the solid-state material is a component of a solid-state structure according to claim 14.

Citation Information

Patent Citations

  • Solid electrolyte compact, process of manufacturing the same, and all solid battery

    JP2014093260A

  • Vitreous solid electrolyte sheet of li-ion conductive sulfur-based glass and related structures, batteries, and methods

    JP2017538266A